Influence of different parameters on dynamic response of nonlinear oscillations - Le, Nguyen Nhat (Vietnam Journal of Mechanics, 1995)
By simulating on personal computer, the nonlinear oscillations with large static deflection of elastic elements have been studied. It is consider the influences of different parameters, in particular, with the numerical value of degrees of smallness. The results at the neighborhood of the original position are accordant with ones of [3].